Protocol to induce cell labeling in vivo and to trace labeled hematopoietic cells using mouse models - Alina Syed; Michihiro Kobayashi; Momoko Yoshimoto (STAR Protocols)
Summary: A combination of hematopoietic stem cell (HSC)- and endothelial cell (EC)-lineage-tracing mouse models enables us to determine blood cell origins. We present a protocol to induce cell labeling in vivo and to trace labeled hematopoietic cells to segregate their origins. We describe the steps for harvesting various hematopoietic tissues, antibody staining, and analyzing the Tomato+ percentages within each immune cell population. We also show how to estimate HSC- and EC-derived percentages of the target cell populations.For complete details on the use and execution of this protocol, please refer to Kobayashi et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.